OP0172 Inflammation and fatty degeneration are of similar importance for new bone formation in patients with ankylosing spondylitis treated with infliximab or other anti-TNF agents over 5 years. (23rd January 2014) - Baraliakos, X.; Heldmann, F.; Callhoff, J.; Listing, J.; Appelboom, T.; Brandt, J.; van den Bosch, F.; Breban, M.; Burmester, G.; Dougados, M.; Emery, P.; Pappas, D.; et al.
Abstract : Background: The nature of the effect of anti-TNF therapy on new bone formation in ankylosing spondylitis (AS) is still obscure. Clinical trial results suggest that new bone formation is neither inhibited nor augmented by anti-TNF agents. This is the first study to analyse inflammation (INF) and fatty degeneration (FD) as assessed by magnetic resonance imaging (MRI) and syndesmophyte formation as assessed by conventional radiography in vertebral edges (VE) of patients treated with anti-TNF agents at baseline (BL), and after 2 and 5 years (y). Objectives: To directly compare the influence of INF and/or FD on the development of syndesmophytes in AS patients after 2 and 5y of anti-TNF therapy. Methods: An experienced reader who was blinded for the time point of investigation scored MRIs and x-rays of patients who participated in EASIC. Most patients were treated with infliximab. Presence or absence of INF, FD and syndesmophytes was documented on the level of VEs in the anterior part of the spine. Data were compared using Fisher's exact test. Results: Complete sets of MRIs and x-rays of 73 AS patients were evaluated at 2 and 5y (1, 062 VEs, 258 with and 804 without syndesmophytes or ankylosis at BL). The amount of VEs with INF decreased significantly from 22% at BL (n=177) to 2% after 2 (n=17) and 5y (n=16), respectively. In contrast, the amount of VEs with FD increased from 23.5% (n=189) at BL to 35.2% at 2y (n=283) and to 36.8% at 5y (n=296). In parallel, new syndesmophytes developed in 1.7% (n=14) at 2y and in 3.4% (n=27) at 5y. Syndesmophytes at BL showed FD in 59.1% (n=143). There was no evidence of an influence of either INF or FD on the development of syndesmophytes in 43% after 2 and in 48% after 5y. At 2y, 8/14 new syndesmophytes were preceded by INF (n=4) or FD (n=4) at BL with both being present in 3 cases, while at 5y 14/27 new syndesmophytes were preceded by INF (n=6) or FD (n=8) at BL with both being present in 3 cases. There was a trend to more syndesmophyte development in VEs with than without FD at BL: 2.1% (n=4) vs. 1.6% (n=10) at 2y and 4.2% (n=8) vs. 3.1% (n=19) at 5y, respectively. In comparison, syndesmophytes developed in 2.3% (n=4) vs. 1.6% (n=10) at 2y and in 3.4% (n=6) vs. 3.3% (n=21) at 5y of VEs which had shown inflammation at BL. Conclusions: In patients with AS treated with anti-TNF agents over 5 years, both, spinal inflammation and fatty degeneration were slightly associated with syndesmophyte development in this study. However, almost 50% of the new bone formation observed in patients treated with anti-TNF agents over 5 years was not preceded by either one of those. Finally, rather few syndesmophytes developed over 5 years in the patients on anti-TNF therapy (3.4% of all VEs). Disclosure of Interest: None Declared